Convective radiofrequency water vapor thermal therapy for benign prostatic hyperplasia: a single office experience. Issue 3 (September 2018) - Mollengarden, Daniel; Goldberg, Kenneth; Wong, Daniel; Roehrborn, Claus
Abstract Background Convective radiofrequency water vapor thermal therapy with the Rezūm system is a relatively new treatment for benign prostatic hyperplasia (BPH). We present results from a single surgeon in an office setting. Methods A retrospective review of 129 patients from a single surgeon who underwent the Rezūm procedure was performed. All patients were at least 4 months out from treatment. International prostate symptom scores (IPSS), maximum flow rates (Qmax), residual urine volumes, medication usage, and adverse events were monitored. Data were analyzed at baseline, 15–45 days, 46–90 days, and 91–180 days after treatment. A scripted patient questionnaire was attempted over the phone to all patients. It was administered by a resident and medical student who do not work in the provider's office. Results Maximal effects were noted at the 91–180 day interval. IPSS improved from a baseline of 18.3 to 6.9 and Qmax from 10.5 to 16.8 mL/s. Improvements were independent of starting symptom score, median lobe treatment, and prostate size. There was a 17% prostate volume reduction based on TRUS and 14% based on PSA. The most common adverse events were urinary tract infections (17%) and transient urinary retention (14%). In total 90% of patients were able to come off their BPH medications and 86% of patients would recommend the procedure to a friend. Conclusions Rezūm radiofrequency water vapor thermal therapy offers a minimally invasive option for BPH management with moderate improvement in symptoms and flow rate. The results appear to be independent of prostate size or presence of a median lobe, and have now been replicated in a single office setting.